Research on Diversified Visual Communication Design Based on Computer Digital Technology. (11th October 2022) - Liu, Hui; Zhang, Zhiliang; Pan, Youcheng
Abstract : In order to improve the effect of diversified visual communication, this paper combines computer digital technology to design a multidimensional visual communication system. In order to improve lighting performance, parts of the surface of the secondary processing visually conveyed image have been processed with different diffusing materials, and the effects have been compared in simulations. There are two types of simulations: external simulation and internal simulation. Moreover, the cutting method based on the shape of the lighting area can design a rectangular lighting area, and the diffusing material can improve the lighting performance to a certain extent. In addition to this, according to the shape of the set target plane, a cut visual communication image is obtained. Through multiple simulation experiments, this paper verifies that the diversified visual communication design system based on computer digital technology can effectively improve the visual communication effect.